БЕНЧМАКІНГ ЯК ПРОЕКНИЙ ІНСТРУМЕНТ КОНКУРЕНТОСПРОМОЖНОСТІ В СУЧАСНОМУ БІЗНЕСІ - Vikarchuk, Olga; Zavalii, Tetiana; Kalinichenko, Olena (Zhytomyr Ivan Franko State University, 2022)
The definition of the category “benchmarking” is examined and clarified in this article. The underlying aims and characteristics of the application of benchmarking as a project tool for searching as well as justifying management decisions regarding the increase of competitiveness of the business are considered. The scientific concepts of defining the essence of benchmarking as an economic category are presented. It is established that there are numerous ways of interpreting this very definition. A universal approach should be specified, since currently benchmarking is not only used for enterprises, but also within the organization and management of individual areas. Two approaches on how to interpret the definition of benchmarking are suggested, namely a static and a dynamic one. On the one hand, it allows to define benchmarking as a management method and, on the other, as a constant and changing process determined by external and internal factors. Consequently, it is proposed to consider benchmarking as a management method, the essence of which is to highlight the most outstanding outcomes of economic agents (primarily business entities) and utilize it in the performance of other enterprises, institutions, and organizations. The intention behind the use of benchmarking in the business activities is justified and the main stages of its implementation at the enterprises are determined. It is concluded that the use of benchmarking yields marginal efficiency and effectiveness of the business processes, increases productivity and quality of the services; enhances competitiveness and marketing effectiveness; improves the utilization of resources as well as supports the quality of the management and optimal management decisions-making. It is shown that benchmarking has been widely established in Ukraine, yet. The major underlying causes are the lack of a unified conceptual tool, the unavailability of information, the lack of developed cooperation and partnerships as well as the reluctance towards innovations in the management processes. Nevertheless, the utilization of benchmarking provides a unique competitive advantage and successful operation of a business entity in the long run.